2018
DOI: 10.24123/jmb.v15i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Improving Service Quality of Call Center Using Dmaic Method and Service Blueprint

Abstract: Customer satisfaction is an important factor to businesses, because it causes customers to constantly return to use the service. Customer satisfaction is also related to the quality of service received by the customer of the companys’ products or services. The problem of OC’s call center service quality happened at the first time a customer contacts the call center where waste of customer’s waiting time is detected. Service quality improvement methods used in the analysis of the waste of customers’ waiting tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Alsyouf et al ( 2014 ) conducted a study in one of the international airports using the DMAIC method to identify the reasons for mishandled baggage. Abdul and Purwatmini ( 2016 ) applied the DMAIC method to improve the quality of call centre service as well as the service blueprint tool to analyse the relationship between quality improvement using DMAIC, customer contact and evidence from customer service. In India, Gupta et al ( 2018 ) used the DMAIC methodology to enhance the tire manufacturing process by reducing the number of defective items.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alsyouf et al ( 2014 ) conducted a study in one of the international airports using the DMAIC method to identify the reasons for mishandled baggage. Abdul and Purwatmini ( 2016 ) applied the DMAIC method to improve the quality of call centre service as well as the service blueprint tool to analyse the relationship between quality improvement using DMAIC, customer contact and evidence from customer service. In India, Gupta et al ( 2018 ) used the DMAIC methodology to enhance the tire manufacturing process by reducing the number of defective items.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, although DMAIC methodology was originally used in manufacturing processes, it has also been widely applied within many service industries, especially financial and healthcare institutions (Siha and Saad, 2008). In the context of the service industry, DMAIC methodology can be utilized to manage customers' dissatisfaction within the business process as certain issues are identified, variables affecting process are quantified, sources of the problems are analyzed, improvement is de-signed and implemented, variables are monitored until the expected sigma level is attained, and customer satisfaction is optimized (Abdul and Purwatmini, 2018). Implementation of this method in a healthcare service company was reported to generate significant cost savings and improvement at the sigma level (Rohini and Mallikarjun, 2011).…”
mentioning
confidence: 99%
“…Large numbers of successful Six Sigma projects in the hospitality industry were reported that demonstrated improvement in productivity, menu redesign, resort concierge, e-mail marketing, waiting for time, billing error, occupancy rate, and sales (Chakraborty and Tan, 2012). Abdul and Purwatmini (2018), also found that the five stages of DMAIC reduced loss caused by the withdrawal of customer loyalty from unhappy customers who got bad experience with the service. This reduction led to an improvement in the service quality of a call center company.…”
mentioning
confidence: 99%
“…Quality means more than simply meeting the customer's expectations. It means meeting or exceeding the customer's implied or perceived expectations to provide value (Abbott, 2004) as the quality of service affects customers' satisfaction (Abdul & Purwatmini, 2018). The BPO industry practices quality assurance as well.…”
Section: Introductionmentioning
confidence: 99%